Association between added sugars and kidney stones in U.S. adults: data from National Health and Nutrition Examination Survey 2007–2018 - Yin, Shan; Yang, Zhenzhen; Zhu, Pingyu; Du, Zhongbo; Yu, Xiaodong; Tang, Tielong; Borné, Yan (Frontiers in Nutrition, 2023)
Purpose Added sugar is associated with a variety of adverse health outcomes, but its association with kidney stones is unclear. This study was to determine whether added sugar is associated with kidney stones.This nationally representative study used National Health and Nutrition Examination Survey (NHANES) datasets from 2007 to 2018 for analysis.People aged ≥ 20 years who reported a history of kidney stones and provided dietary recall data on added sugars were included. Weighted proportions, multivariable logistic regression analysis and stratified logistic regression were used to evaluate the associations between added sugars and kidney stones by adjusting potential confounders.Totally 28 303 adults were included, with weighted mean age (95% confidence interval (CI)) of 48.03 (47.56, 48.51) years, 47.74% (47.09%, 48.40%) males and 52.26% (51.60%, 52.91%) females. The overall mean (95%CI) energy intake from added sugars was 272.10 (266.59, 277.60) kilocalories. In the fully-adjusted multivariable model, the percentage of energy intake from added sugars was positively correlated with kidney stones. Compared to the first quartile of added sugar energy intake percentage, the population in the fourth quartile had a higher prevalence of kidney stones (OR = 1.39; 95%CI 1.17 to 1.65). Compared with the less than 5% calories from added sugar population, the more than or equal to 25% calories from added sugar had a higher kidney stone prevalence (OR = 1.88; 95%CI 1.52 to 2.32).Conclusions A higher percentage of energy intake from added sugars is significantly associated with a higher prevalence of kidney stones. This study provides crosssectional evidence for the relationship between added sugars and health outcomes.